Proyecto de factibilidad para la creación de la empresa de servicios “Mandatitos.com” entregas a domicilio (delivery) en la ciudad de Loja - Suquilanda Montoya, Catalina Elizabeth (2023)
This research aims to determine the feasibility of home delivery service in the company "MANDADITOS .COM" in the city of Loja. As people need to make household purchases but do not have time, an idea was born to provide a home delivery service that solves their lives, saving them time, avoiding long lines, and allowing them to do so from wherever they are using only their cell phone and an Internet connection. The purpose of this study is purely descriptive; in addition, interviews, surveys, and direct observation techniques were designed to segment the population. A total of 384 surveys were conducted with Loja families in urban areas, where the unsatisfied demand was identified as 226,993 Delivery services, finally the company's marketing plan was established to compete in the market. The capacity utilized will be 9,984 home delivery services per year and a market share of 51% during the first year. It was determined that an investment of US$15,369.60 is required to start up the home delivery service plant. Through cost analysis, the retail price was determined, resulting in a market price of $1.50 dollars. Regarding the financial indicators: Net Present Value (NPV) had a positive result of $ 15,647.00, the Internal Rate of Return (IRR) was 62%, the Benefit-Cost Ratio (BCR) was obtained that for every dollar invested, 1.27 cents of profitability was obtained. The Capital Recovery Period (CRP) will be recovered in 1 year, 5 months and 26 days, and finally in the Sensitivity Analysis the maximum percentage increase in costs is 8.55% and its maximum decrease in income is 14.67%, thus the project is not sensitive to these variations that can influence its profitability. Based on its financial indicators, this investment project has been determined to be feasible for execution. The implementation of this strategy is recommended since it will produce profitability and economic benefits once it enters the operational phase.